Microbial Isolates in Microplastic-Polluted Soil - Battah, Moses Victor; Olawale, Otitoju; Abah, Moses; John, Umaru Isaac; Dauda, Maianguwa Abdulrashid; Joel, Emmanuel Askeb-nde; Vera, Caleb; Umaru, Kerenhappuch Isaac (African Journal of Biochemistry and Molecular Biology Research, 2024)
Microplastic pollution is a growing environmental concern, with plastic debris fragmenting into microscopic particles that contaminate soil ecosystems. Microplastics have become a major environmental concern due to their persistent presence in various ecosystems, including soil. They can act as pollutants and have detrimental effects on the environment and human health. This study aimed at isolating and identifying microbes (Bacteria and Fungi species) present in microplastic-polluted soil. Microplastic-polluted soil samples were collected from three sites (which were Kwararafa University Area Wukari to serve as the site 1, Federal Road Safety Commission Office Area Wukari to be the site 2, while Marmara Area Wukari to be the site 3), from two points; A and B and then packaged in brown envelopes which were then transferred to the Laboratory for further analysis after air-drying them for 24 hours. Then 1gram of each soil sample was weighed and suspended in 9mls of distilled water respectively; Six (6) folds of distilled water were prepared for serial dilution of each soil sample. 1ml of each sample was pour plated on NA, MAC, BA, EMB, CLED and SDA respectively. Then a smear of bacteria was prepared and allow to air dry for 30min and heat fix using flame after which was viewed under the microscope. The results obtained from this study showed that Staphylococcus spp are large, medium, small, and pinpoint in size, irregular and spherical in shape, light pink, creamy grey in color, smooth, mucoid and dried texture. Escherichia coli and Klebsiella spp here has similar morphological characteristics, both in size, shape, color, texture, margin and elevation as Staphylococcus spp. Bacillus spp and Pseudomonas spp here has similar morphological identification but differ only in their shape where Bacillus spp has a filamentous shape but Pseudomonas spp has rhizoid shape respectively. In terms of texture, Bacillus spp are Smooth, dried and mucoid but Pseudomonas spp are only smooth, dried texture. Bacillus spp and Pseudomonas spp only differ in their cell morphology where Bacillus spp appears to be rods with spores while Pseudomonas spp appears as short and long rods in pairs. They react positive to catalase, oxidase and citrate tests while negative to indole test. Aspergillus Niger and Rhizopus stolonifer were found to be the major fungi isolated from the collected sample. Aspergillus Niger and Rhizopus stolonifer are spherical in shape and are large in size. Aspergillus Niger appears powdery and Rhizopus stolonifer appears to fluffy, wood-like. In terms of color and pigmentation Aspergillus Niger species are black, black creamy on reverse while Rhizopus stolonifer appears grayish in color. The discovery of these microbes in microplastics-polluted soil offers a ray of hope for mitigating plastic pollution. By delving deeper into their capabilities and fostering collaboration between microbiologists and environment. This research will contribute to a broader understanding of the ecological impact of microplastics on soil health and functioning. By identifying microbes associated with microplastics, the specific mechanism of action employed by these bacteria in degrading microplastics can be studied subsequently.